Extrahepatic Anomalies in Infants With Biliary Atresia: Results of a Large Prospective North American Multicenter Study - Schwarz, Kathleen B.; Haber, Barbara H.; Rosenthal, Philip; Mack, Cara L.; Moore, Jeffrey; Bove, Kevin; Bezerra, Jorge A.; Karpen, Saul J.; Kerkar, Nanda; Shneider, Benjamin L.; Turmelle, Yumirle P.; Whitington, Peter F.; et al. (Hepatology (Baltimore, Md.), 2013)
The etiology of biliary atresia (BA) is unknown. Given that patterns of anomalies might provide etiopathogenetic clues, we used data from the North American Childhood Liver Disease Research and Education Network to analyze patterns of anomalies in infants with BA. In all, 289 infants who were enrolled in the prospective database prior to surgery at any of 15 participating centers were evaluated. Group 1 was nonsyndromic, isolated BA (without major malformations) (n = 242, 84%), Group 2 was BA and at least one malformation considered major as defined by the National Birth Defects Prevention Study but without laterality defects (n = 17, 6%). Group 3 was syndromic, with laterality defects (n = 30, 10%). In the population as a whole, anomalies (either major or minor) were most prevalent in the cardiovascular (16%) and gastrointestinal (14%) systems. Group 3 patients accounted for the majority of subjects with cardiac, gastrointestinal, and splenic anomalies. Group 2 subjects also frequently displayed cardiovascular (71%) and gastrointestinal (24%) anomalies; interestingly, this group had genitourinary anomalies more frequently (47%) compared to Group 3 subjects (10%). Conclusion: This study identified a group of BA (Group 2) that differed from the classical syndromic and nonsyndromic groups and that was defined by multiple malformations without laterality defects. Careful phenotyping of the patterns of anomalies may be critical to the interpretation of both genetic and environmental risk factors associated with BA, allowing new insight into pathogenesis and/or outcome. (Hepatology 2013;58:1724–1731)